ANALISIS KEBUTUHAN MODAL KERJA PADA CV. KARYA MAKMUR DI KOTA SAMARINDA - ., Zulkifli (EKONOMIA, 2013)
CV. Karya Makmur in the operations based on the orders from customers, then the size of the company's activities depend on how large the number of orders received, though from the information on the amount of orders received in the previous year showed a relatively increasing trend, and in 2011 the company has provided working capital of Rp415.199.500, - (at current asset balance at December 31, 2011. while for the year 2012 increased to Rp435.959.475, - the purpose of this research study and analyze working capital requirements in 2013 by CV. Karya Makmur In the city of Samarinda in order to run their business smoothly and to take action in order to improve efficiency in particular the use of the company's capital.Basic theory used by the Financial Accounting allegedly hypothesis that existing working capital amounted Rp435.959.475 not meet the working capital requirements for the year 2013 on the CV. Karya Makmur In Samarinda, To prove the hypothesis using the method of analysis tools turnover (turnover) working capital and sales forecasting.Based on the analysis and discussion of the conclusions of this study as follows:Calculation results forecast sales in 2013 amounted to Rp2.026.437.700, - while the available working capital (current assets on the balance sheet in 2012) amounted to Rp435.959.475, - and the working capital required is based on the analysis of Rp596.629.776, 36, - means there is a shortage of working capital to finance the company's operations in 2012 amounted to Rp160.670.301, 36, - or 26.93% (rounded up 27%).